2015
DOI: 10.1080/17470218.2014.1000346
|View full text |Cite
|
Sign up to set email alerts
|

Trial-by-trial adjustments in control triggered by incidentally encoded semantic cues

Abstract: Cognitive control mechanisms provide the flexibility to rapidly adapt to contextual demands. These contexts can be defined by top-down goals-but also by bottom-up perceptual factors, such as the location at which a visual stimulus appears. There are now several experiments reporting contextual control effects. Such experiments establish that contexts defined by low-level perceptual cues such as the location of a visual stimulus can lead to context-specific control, suggesting a relatively early focus for cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This suggests that a spatial location can come to serve as a bottom-up predictive cue for retrieving a context-appropriate top-down control set (for additional discussion, see Crump et al, 2017;Hutcheon and Spieler, 2017). Other recent studies have demonstrated this type of modulation of the congruency effect using a wide variety of different contextual cues, including stimulus location Corballis & Gratton, 2003;Crump, 2016;Crump et al, 2017;Crump, Gong, & Milliken, 2006;Hübner & Mishra, 2016;King, Korb, & Egner, 2012;Weidler & Bugg, 2016), font (Bugg, Jacoby, & Toth, 2008;Crump, 2016), shape (Crump, Vaquero, & Milliken, 2008), color (Vietze & Wendt, 2009), social categories (Cañadas, Rodríguez-Bailón, Milliken, & Lupiáñez, 2013) and incidental sematic cues (Blais, Harris, Sinanian, & Bunge, 2015). This kind of learned contextual modulation of congruency effects, where the frequency of congruent/incongruent trials is linked to an incidental contextual feature of the task, is referred to as the context-specific proportion congruent (CSPC) effect.…”
Section: Behavioral Evidence For Context-control Learningmentioning
confidence: 90%
“…This suggests that a spatial location can come to serve as a bottom-up predictive cue for retrieving a context-appropriate top-down control set (for additional discussion, see Crump et al, 2017;Hutcheon and Spieler, 2017). Other recent studies have demonstrated this type of modulation of the congruency effect using a wide variety of different contextual cues, including stimulus location Corballis & Gratton, 2003;Crump, 2016;Crump et al, 2017;Crump, Gong, & Milliken, 2006;Hübner & Mishra, 2016;King, Korb, & Egner, 2012;Weidler & Bugg, 2016), font (Bugg, Jacoby, & Toth, 2008;Crump, 2016), shape (Crump, Vaquero, & Milliken, 2008), color (Vietze & Wendt, 2009), social categories (Cañadas, Rodríguez-Bailón, Milliken, & Lupiáñez, 2013) and incidental sematic cues (Blais, Harris, Sinanian, & Bunge, 2015). This kind of learned contextual modulation of congruency effects, where the frequency of congruent/incongruent trials is linked to an incidental contextual feature of the task, is referred to as the context-specific proportion congruent (CSPC) effect.…”
Section: Behavioral Evidence For Context-control Learningmentioning
confidence: 90%
“…Nouns preceded the adjectives, in accordance with the Hebrew syntax (examples in this manuscript are provided in the reverse order in favor of fluency and compatibility with the English syntax). List-based distinctiveness was parametrically modulated via the proportion of the familiar and novel stimuli in different experimental lists (Icht, Mama, & Algom, 2014; see also list-wise proportion manipulation in attention and semantic priming; Blais, Harris, Sinanian, & Bunge, 2015;Bugg & Crump, 2012;Tweedy, Lapinski, & Schvaneveldt, 1977). A subsequent surprise noun recognition test was utilized to examine memory effects for items encoded with a familiar or a novel adjective.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, responses for incongruent stimuli are slower than responses for congruent stimuli; however, as the proportions of incongruent words increases, reaction time for these words decreases and approaches that of congruent words (Logan & Zbrodoff, 1979). This "Proportion Congruent" (PC) effect is generally considered evidence in favor of increased availability of attentional control as the experimental proportion of control-demanding stimuli increases (Bugg & Crump, 2012), and has been demonstrated even when in/congruency was based on semantic aspects of stimuli such as higher-level category (Blais et al, 2015; see also Hutchison, 2007). Our results bear strong conceptual resemblance to the PC findings -as the proportion of conceptually novel stimuli in a specific list increased, responses became faster, suggesting increased availability of attentional control.…”
Section: The Effect Of Experimental Proportions On Novel Eventsmentioning
confidence: 99%
“…Distinctiveness was parametrically modulated via the proportion of the familiar and novel stimuli in the experimental list (Icht, Mama, & Algom, 2014; see also list-wise proportion manipulation in attention and semantic priming; Blais, Harris, Sinanian, & Bunge, 2015;Bugg & Crump, 2012;Tweedy, Lapinski, & Schvaneveldt, 1977). A subsequent surprise noun recognition test was utilized to examine memory effects for items encoded in a familiar or in a novel context.…”
Section: Introductionmentioning
confidence: 99%